Un recorrido por los Derechos colectivos en la jurisprudencia argentina (2015)
The Argentina case law and legislation recognizes the legal protection ofcollective rights mandated by the constitutional reform of 1994, s 43,44 and 46, which have been developed by the Supreme Court of the Nation in its judicial pronouncements , since they have established the extent of constitutional articles mentioned, such as standing in collective matter.